Proceedings (111) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Smallholder horticulture in Zimbabwe is the proceedings of a workshop held in August/September 1994, Harare, Zimbabwe edited by J E Jackson, A D Turner and M L Matanda 1997229 pp - ISBN 0 908307 61 6University of Zimbabwe Publications, PO Box MP203,...